The Application of Scanning Electron Microscopy with Energy-Dispersive X-Ray Spectroscopy (SEM-EDX) in Ancient Dental Calculus for the Reconstruction of Human Habits. (20th November 2017) - Fialová, Dana; Skoupý, Radim; Drozdová, Eva; Paták, Aleš; Piňos, Jakub; Šín, Lukáš; Beňuš, Radoslav; Klíma, Bohuslav
Abstract: The great potential of scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) is in detection of unusual chemical elements included in ancient human dental calculus to verify hypotheses about life and burial habits of historic populations and individuals. Elemental spectra were performed from archeological samples of three chosen individuals from different time periods. The unusual presence of magnesium, aluminum, and silicon in the first sample could confirm the hypothesis of high degree of dental abrasion caused by particles from grinding stones in flour. In the second sample, presence of copper could confirm that bronze jewelery could lie near the buried body. The elemental composition of the third sample with the presence of lead and copper confirms the origin of individual to Napoleonic Wars because the damage to his teeth could be explained by the systematic utilization of the teeth for the opening of paper cartridges (a charge with a dose of gunpowder and a bullet), which were used during the 18th and the 19th century AD. All these results contribute to the reconstruction of life (first and third individual) and burial (second individual) habits of historic populations and individuals.